Effect of taste genetic determinants on oral fatty taste sensitivity and perception among obese and non-obese subjects - Bahauddin, Ahmad Riduan; Karim, Roselina; Shaari, Nazamid; Mohd Shariff, Zalilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Several studies on oral fat sensitivity and acceptance were associated with variant of CD36 gene, genetic ability in tasting 6-n-propylthiouracil (PROP) and also obesity risks. However, little is known about those relationship and function between lean and obese individuals. Therefore, this research is carried out to analyse the relationship between CD36 gene variants and PROP taster status towards fatty taste sensitivity and preference amongst lean and obese individuals. A total of 88 obese and 92 lean subjects aged 20-45 were classified into PROP nontasters, medium tasters, or supertasters by using PROP filter paper screening procedure. Suprathreshold sensitivity for linoleic acid solutions, intensity and liking rating towards 2 food products (gravy dessert and pudding) at different fat content was assessed using general/hedonic Labeled Magnitude Scales. All the subjects were genotyped for CD36 gene variants (SNPs: rs1761667, rs152748 and rs1049673). Overall, obese subjects had a higher degree of acceptability for higher concentrated fatty foods compared to lean subjects. Oral fatty sensitivity was correlated to CD36 gene variant (SNPs: rs1761667) and PROP taster status (p<0.05). Subjects with AA homozygous for rs1761667 and also supertaster had lower acceptability towards high fatty content product compared to G allele carriers for rs1761667 in both lean and obese subjects (p<0.05). These findings suggested that PROP taster status and CD36 gene variation could play a significant role in oral fatty sensitivity and perception in obese and non-obese subjects.